Multivariate Cointegration Analysis On Indonesia, Malaysia, and Singapore Stock Exchange - Amsal Irmalis; Fajri Hadi; Muzakir Muzakir (Proceedings of AICS - Social Sciences, 2019)
This study aims to examine the stock market cointegration between The Indonesia Stock Exchange (IDX), The Malaysia Stock Exchange (Bursa Malaysia) and The Singapore Stock Exchange (SGX). This research uses multivariate analysis for only 3 stock exchanges rather than a large number of stock exchanges. Weekly stock index prices from each capital market covering January 2013 to December 2018 are used and The data is analysed using the Johansen testing approach with the Vectorautoregresiv (VAR) framework. ADF test is used to check the data series stationarity. It is found that the data series employed in this research are non-stationary at level, yet stationary in the first difference I(1). The trace statistics and maximum-eigen statistics exhibit a smaller value than the critical value at 5% significance level. This result confirms that by multivariate analysis, when all series of data was tested at the same time, there is no cointegration between Indonesia, Malaysia and the Singapore Stock Exchange. Meaning that, in the long term, the effects of changes in one of the stock price indices do not affect on the price of stock indices in two other countries in a multivariate manner. Besides, the finding also suggests that diversification strategy to reduce risk and the possibility to gain abnormal returns are still visible for investors investing in Indonesia, Malaysia and Singapore Stock Exchange.